2018
DOI: 10.1017/pen.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

On Curiosity: A Fundamental Aspect of Personality, a Practice of Network Growth

Abstract: Human personality is reflected in patterns—or networks—of behavior, either in thought or action. Curiosity is an oft-treasured component of one’s personality, commonly associated with information-seeking proclivities with distinct neurophysiological correlates. The markers of curiosity can differ substantially across people, suggesting the possibility that personality also determines the architectural style of one’s curiosity. Yet progress in defining those styles, and marking their neurophysiological basis, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 106 publications
(145 reference statements)
0
33
0
Order By: Relevance
“…The everyday behaviors through which curiosity is theorized to lead to the accruement of psychological resources remain to be characterized. Emerging perspectives conceive of curiosity as a knowledge network building practice in which concepts and the connections between them are added and taken away during the intrinsic information-seeking that characterizes curiosity (54,55). This knowledge network building perspective calls for a greater consideration of everyday curiosity behaviors and presents new tools from network science to formally study the manner in which curiosity drives knowledge network growth.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The everyday behaviors through which curiosity is theorized to lead to the accruement of psychological resources remain to be characterized. Emerging perspectives conceive of curiosity as a knowledge network building practice in which concepts and the connections between them are added and taken away during the intrinsic information-seeking that characterizes curiosity (54,55). This knowledge network building perspective calls for a greater consideration of everyday curiosity behaviors and presents new tools from network science to formally study the manner in which curiosity drives knowledge network growth.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A forma mentis network consists of words as nodes, each with a valence attribute, and free associations as links. Rather than being based on automatic natural language processing, these networks directly access the mental lexicon of human participants, addressing the orthogonal influences of semantic knowledge and emotional affect that drive the processing of information Vitevitch, 2008;Vitevitch et al, 2018) and its consequent reactions (Adelman & Estes, 2013;Christensen et al, 2018;Gaillard et al, 2006;Zurn & Bassett, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Psycholinguistic evidence has shown that the associative structure of the mental lexicon influences language processes such as word learning (Hills & Siew, 2018;Stella, 2019;Stella, Beckage, & Brede, 2017) and processing (De Deyne, Navarro, & Storms, 2013;De Deyne, Navarro, Perfors, Brysbaert, & Storms, 2018;Kenett, Levi, Anaki, & Faust, 2017;Steyvers & Tenenbaum, 2005). This strong link between mental lexicon structure and language usage promoted the use of network models for a variety of processes such as the discovery of writing styles from word co-occurrences in texts (Amancio, 2015) or predicting the creativity of individuals (Kenett, Anaki, & Faust, 2014;Kenett et al, 2018), their curiosity (Zurn & Bassett, 2018), their openness to new experience (Christensen, Kenett, Cotter, Beaty, & Silvia, 2018), their expertise in a given domain (Siew, 2018;Valenzuela Castellanos, Pérez Villalobos, Bustos, & Salcedo Lagos, 2018) and their perceived anxiety toward a topic (Siew, McCartney, & FORMA MENTIS NETWORKS IN STEM 6 Vitevitch, 2019). Forma mentis networks rely on the framework of cognitive network science to represent the associative and emotional structure of concepts in the mental lexicon.…”
Section: Introductionmentioning
confidence: 99%
“…The hunter instead "wishes [they] had a few hundred helpers and good, well-trained hounds that [they] could drive into the history of the human soul to round up [their] game" 22 (p.59) in a targeted search for information. Both styles are considered curious practice, but there are individual differences in the extent to which each type of curious practice is expressed in behavior 23 . Tendencies to exhibit one form of curiosity practice over another will lead to the accumulation of different types of information and resources over time.…”
Section: Introductionmentioning
confidence: 99%